STRATEGI BERTAHAN HIDUP PETANI PADI SAWAH PASCA KERUSAKAN BENDUNGAN IRIGASI KRUENG PASE DI GAMPONG KEUTAPANG KECAMATAN SYAMTALIRA ARON - Riani, Riani; Martina, Martina; Salamah, Salamah; Barmawi, Barmawi; Zuriani, Zuriani (LPPM Universitas Malikussaleh - Indonesia, 2025)
Paddy rice production in Aceh Utara has seen a decrease over the years, with production dropping from 427,455 tons in 2019 to 388,190 tons in 2021. One of the main reasons for this decline is the damage to the Krueng Pase irrigation dam. Despite the challenges, farmers in the area have adapted by adjusting to the limited water supply and the rainy season. Some farmers choose not to engage in agricultural activities during the dry season, requiring them to employ survival strategies. This study focuses on determining the survival strategies of wet-rice farmers in Keutapang Village, Syamtalira District, Aceh Utara following the damage to the Krueng Pase irrigation dam. The research area was selected using purposive sampling, where 30 farmers were selected using simple random sampling. The data was analyzed using qualitative descriptive analysis and a Likert scale. The results of the study revealed that active strategies such as job diversification and family member contribution were rated as strong, while the passive strategy of frugal lifestyle obtained a very strong rating, and the savings strategy was rated as strong. Network strategies were also identified, but their rating was not provided in the summary.